SIGMOID COLON HEMANGIOMA IN CHILDHOOD: A CASE REPORT - Agil, Nadifa; Astien, Astien; Wahab, Revalita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2025)
Hemangioma of the gastrointestinal tract is an uncommon benign vascular tumor. The unspesific clinical sign makes it hard to recognize, thus the clinicians often misdiagnose the disease. This article describes a case of a 2‐years‐old girl who developed recurrent abdominal pain, chronic anemia, and mild abdominal distention that’s tender with a hardness on palpation in the suprapubic region and the inability to urinate. Laboratory results shows low hemoglobin level.Abdominal ultrasound examination revealed a Douglas pouch abscess or ovarian cyst. The CT scan impression indicates a cystic mass in the Douglas pouch that is compressing the rectosigmoid, possibly indicating an ovarian cyst. Although a diagnosis of sigmoid colon hemangioma is rare and presents itself with non-specific symptoms, this condition should be considered in the differential diagnosis of abdominal tumors in children.